1999
DOI: 10.1021/jf990591g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Bovine β-Lactoglobulin A, B, and C Explored Using Thiol Availability and Fluorescence

Abstract: Dilute solutions of beta-lactoglobulin (beta-Lg) A, B, and C were heated at temperatures between about 40 and 94 degrees C for 10 min, cooled, and analyzed using Trp fluorescence and extrinsic fluorescence spectra of the probe 1,8-anilinonaphthalene sulfonate (ANS). Thiol availabilities using 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB) were determined using a separate set of samples. The normalized ANS fluorescence emission intensity and the thiol availability results showed a 1:1 relationship with the loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
61
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 36 publications
10
61
0
1
Order By: Relevance
“…This study confirmed that intrinsic fluorescence intensity of WPI increased and the red shifts in the emission spectra are apparently due to the unfolding of the whey protein resulting during PEF treatment. This result is consistent with the results observed by Manderson et al (1998) and Moro et al (2001) for thermal processing. Increases in the intrinsic fluorescence intensities and red shifts observed after PEF treatments indicated changes in the polarity of tryptophan residues microenvironment in whey proteins from a less polar to a more polar environment.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This study confirmed that intrinsic fluorescence intensity of WPI increased and the red shifts in the emission spectra are apparently due to the unfolding of the whey protein resulting during PEF treatment. This result is consistent with the results observed by Manderson et al (1998) and Moro et al (2001) for thermal processing. Increases in the intrinsic fluorescence intensities and red shifts observed after PEF treatments indicated changes in the polarity of tryptophan residues microenvironment in whey proteins from a less polar to a more polar environment.…”
Section: Resultssupporting
confidence: 93%
“…The intrinsic tryptophan fluorescence intensities of WPI increased significantly (P≤0.05) with the increase in electric field intensity ranging from 12, 16, and 20 kV cm −1 . Manderson et al (1998) established that the emission spectra of bovine β-lactoglobulin appeared as red shift when β-lactoglobulin was heated to 85°C. Moro et al (2001) used different techniques to study surface hydrophobicity of whey protein concentrate heated at 85°C.…”
Section: Resultsmentioning
confidence: 99%
“…Matulis and Lovrien [36] reported that electrostatic interactions are the predominant interactions between ANS and bovine serum albumin, and hydrophobic affinity is a minor interaction between them, which is in agreement with our results.…”
Section: The Binding Of Ans To Casein Micellessupporting
confidence: 93%
“…The elution was carried out at a flow rate of 0.8 mL/min with 30 mM sodium phosphate, pH 6.7, or 30 mM glycine, pH 2.5. at 268 nm originating from its phenylalanyl residues and two characteristic deep minima at 287 and 297 nm arising from tryptophanyl residues, especially Trp19. At pH 6.7, the intensity of the two minima, slightly shifted at 286 and 294 nm, increased; a more significant increase of the intensity at 268 nm was observed, which agrees well with the results of Manderson et al [23]. The main b-lactoglobulin fluorescent residue is Trp 19 and is responsible for 80% of the protein fluorescence emission [24].…”
Section: Spectroscopysupporting
confidence: 89%